The byproduct generation analysis of the NOx conversion process in dielectric barrier discharge plasma. Issue 68 (5th July 2016) - Zhang, Yajie; Tang, Xiaolong; Yi, Honghong; Yu, Qingjun; Wang, Jiangen; Gao, Fengyu; Gao, Yueming; Li, Dianze; Cao, Yumeng
Abstract : Abatement of NO x through non-thermal plasma (NTP) processes has been developed over the past several years. Abstract : Abatement of NO x through non-thermal plasma (NTP) processes has been developed over the past several years. Since discharge plasma contains a large amount of highly active species during the reaction process, NO x is removed during our desired conversion reaction, as well as production of other byproducts, such as O3 and N2 O. The effect of reaction conditions, such as oxygen content, discharge power, operation time, initial NO concentration and gas residence time, on generation characteristics of O3 and N2 O was investigated. Results showed that, with increasing oxygen concentration and discharge power, the production of N2 O and O3 increases. Additionally, O3 concentration decreases with increasing operation time; the higher input power, the higher the temperature increases, causing a greater reduction rate of O3, which also leads to a reduction of NO2 production. NO concentration and gas residence time also exert effects on the generation of byproducts.